Spatial Model of Sky Brightness Magnitude in KUSZA Observatory, UniSZA - Umar, Roslan; Jannah Awang, Wardatul; Nadhirah Berzanji, Siti; Farhana Abd Majed, Nur; Khairul Amri Kamarudin, Mohd; Garba Abdullahi, Musa (International Journal of Engineering and Technology, 2018)
Light pollution is the by-product of anthropogenic activities result from the increases in advanced economic and urbanization. Light pollution limits the ability to view the night sky by astronomers, on biodiversity, and ecosystems. This technology nowadays has led us to increase the convenient method to observe the brightness of night sky to determine how much the night sky polluted by artificial light. The study used SQM device and monitored the sky brightness of the KUSZA Observatory in Merang, Setiu, Terengganu, Malaysia. The results obtained were used to compare with the results obtained by simulation data generated from Earth Observation Group (EOG) of National Oceanic and Atmospheric Administration (NOAA), National Geophysical Data Center. It is the first world atlas of the artificial night sky brightness using GIS Interpolation tools. The result showed that the Kusza Observatory Merang is still appropriate to be the place of observation of celestial objects to either optical or radio astronomers. Hence, we recommended that through the data obtained from Defense Meteorological Satellite Program (DMSP) satellites, the value of sky brightness from all over the world can be used to make further analysis and to increase the precision of data recorded through observations. This study provides a clear view mapping of the accessing the sky condition using Geographic Information System (GIS) analysis in the study area.Â Â